Caffeic acid phenethyl ester potentiates gastric cancer cell sensitivity to doxorubicin and cisplatin by decreasing proteasome function. Issue 3 (March 2019) - Matsunaga, Toshiyuki; Tsuchimura, Saeka; Azuma, Nozomi; Endo, Satoshi; Ichihara, Kenji; Ikari, Akira
Abstract : Caffeic acid phenethyl ester (CAPE) is a major propolis component that possesses a variety of pharmacological properties such as antioxidant and anticancer effects. Herein, we investigated the effectiveness of CAPE on cytotoxicity of clinically used anticancer drugs, doxorubicin (DXR) and cisplatin (CDDP), in parental and the drug-resistant cells of stomach (MKN45) and colon (LoVo) cancers. Concomitant treatment with CAPE potentiated apoptotic effects of DXR and CDDP against the parental cells. The treatment significantly reduced the production of reactive oxygen species elicited by DXR but did not affect the DXR-mediated accumulation of 4-hydroxy-2-nonenal, a lipid peroxidation-derived aldehyde. Intriguingly, treatment of parental MKN45 cells with CAPE alone reduced 26 S proteasome-based proteolytic activities, in which a chymotrypsin-like activity was most affected. This effect of CAPE was the most prominent among those of eight flavonoids and nine cinnamic acid derivatives and was also observed in parental LoVo cells. In the DXR-resistant or CDDP-resistant cells, the chymotrypsin-like activity was highly up-regulated and significantly decreased by CAPE treatment, which sensitized the resistant cells to DXR and CDDP. Reverse transcription-PCR analysis showed that CAPE treatment led to downregulation of five proteasome subunits (PSMB1–PSMB5) and three immunoproteasome subunits (PSMB8–PSMB10) in DXR-resistant MKN45 cells. The results suggest that CAPE enhances sensitivity of these cancer cells and their chemoresistant cells to DXR and CDDP, most notably through decreasing proteasome function. Thus, CAPE may be valuable as an adjuvant for DXR or CDDP chemotherapy in gastric cancer. Abstract : Supplemental Digital Content is available in the text.